2016
DOI: 10.1159/000450699
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Lipase during Initial Presentation of Ulcerative Colitis in a Pediatric Patient: Do We Check for It

Abstract: There are very few reports of elevated lipase in pediatric inflammatory bowel disease (IBD). Symptoms of pancreatitis may be masked by abdominal pain in pediatric IBD. During the initial presentation of IBD in our patient, lipase was elevated to more than 3 times the upper limit of normal. Normalization of values coincided with remission of IBD. This may be due to extraintestinal involvement of the pancreas as part of the inflammatory process or due to leakage of pancreatic enzymes from an inflamed gut or medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…There were only few cases of elevated pancreatic enzymes without any other symptoms of pancreatic disease in IBD children in the literature published in English [ 8 , 48 , 49 ]. Based on Martinelli study, 81.2% of patients with hyperamylasemia/hyperlipasemia (HA/HL) manifested active IBD as well as AP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were only few cases of elevated pancreatic enzymes without any other symptoms of pancreatic disease in IBD children in the literature published in English [ 8 , 48 , 49 ]. Based on Martinelli study, 81.2% of patients with hyperamylasemia/hyperlipasemia (HA/HL) manifested active IBD as well as AP.…”
Section: Resultsmentioning
confidence: 99%
“…However, after 12 months follow up 68.7% of patients reached a complete remission in pancreatic involvement. In one case report, HL correlated with severity of UC and lipase activity decreased when remission of UC was achieved [ 49 ]. In other case report, elevated amylase activity was diagnosed as macroamylasemia [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of inflammatory mediators and cytokines released from the inflamed gut on the pancreas may also contribute to pancreatic damage and leakage of pancreatic enzymes into the blood [ 83 , 86 , 87 ]. There are a few reports of elevated lipase in patients with IBD [ 83 , 86 , 88 , 89 ]. The study of Ray and van Arsdall reported that during the initial presentation of IBD in their patients, lipase was elevated to more than three times the upper limit of normal [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports of elevated lipase in patients with IBD [ 83 , 86 , 88 , 89 ]. The study of Ray and van Arsdall reported that during the initial presentation of IBD in their patients, lipase was elevated to more than three times the upper limit of normal [ 89 ].…”
Section: Discussionmentioning
confidence: 99%